IMPLEMENTATION OF RAWLS THEORY OF JUSTICE IN THE DEVELOPMENT OF FOOD ESTATE IN CENTRAL KALIMANTAN - Andhinasari, Ronalia (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2024)
The rapid increase in the world's human population and the threat of a global economic crisis have also led to the threat of a food crisis, which requires action from the government to anticipate the threat of a food crisis and ensure sufficient food availability for the entire community. The food estate program is a national food development program that integrates the agriculture, plantation and livestock sectors in one area, so to implement this program the government needs to provide sufficient land. Forest areas in Central Kalimantan are one of the locations used for the Food Estate program and the land use for the program is guaranteed by Peraturan Menteri Lingkungan Hidup dan Kehutanan No. 24 Tahun 2020 about Provision of Forest Area for Food Estate Development. The results of the study found that the implementation of the program in Central Kalimantan did not run smoothly because it only planted crops according to market demand and changed local commodities that were already running in the area. In addition, the food estate program is also detrimental to indigenous peoples living in Central Kalimantan because of land conversion so that their livelihoods are reduced and even lost. This food estate program cannot meet the criteria of justice such as Rawls' theory of justice, because the program that was created to ensure the welfare of the people at large has instead caused harm to indigenous peoples living in the Central Kalimantan forest area